Evaluation of suitable method of composting castor shell and stalk: EVALUATION OF SUITABLE METHOD OF COMPOSTING CASTOR SHELL AND STALK - S K SHAH; A L JAT; A M PATEL; C J PATEL; K V CHAUDHARY; L D PARMAR (Journal of Oilseeds Research, 2022)
The experiments on evaluating compostingmethod with differenttreatmentswere conducted for four consecutive years at the Castor-Mustard Research Station, S D Agricultural University, Sardarkrushinagar during 2018-21 the nutrient composition of composted castor shell and stalk were examined. The results indicated that composted fresh castor shell or shredded stalk compost (approx. 1000 kg) treated with cow dung (100 kg) + urea solution (4 kg/200 L water) + SSP (5 kg) along with microbial consortium @ 1 kg resulted in highest N, P, K content and micronutrient content (Fe, Mn, Zn and Cu). The cost of production of compost was ` 6.81 per kg of shell and ` 6.76 per kg stalk respectively.